Large reductions in pesticides made possible by use of an insect‐trapping lamp: a case study in a winter wheat‐summer maize rotation system. Issue 7 (12th March 2018) - Guo, Liyue; Muminov, Mahmud Abdimuratovich; Wu, Guanglei; Liang, Xiaotian; Li, Caihong; Meng, Jie; Li, Lijun; Cheng, Da; Song, Yanjie; Gu, Xian; Zhao, Jianshe; Jiang, Gaoming
Abstract: BACKGROUND: Increasing attention is being paid to physical methods to control pests such as insect trapping. In order to examine how pesticides can reasonably be combined with the use of an insect‐trapping lamp and by how much this can reduce the amount of pesticide used, five treatments were applied to a winter wheat–summer maize rotation system in eastern China: a treatment in which only pesticides were used; a treatment with only insect‐trapping lamps; insect‐trapping lamps plus one application of pesticides; insect‐trapping lamps plus two applications of pesticides; insect‐trapping lamps plus three applications of pesticides. RESULTS: The results showed that, when pesticides were reduced by 25–35%, the insect‐trapping lamps controlled the insect population well and yields were not decreased but were actually increased, with pesticides being applied only at 2 days before winter wheat planting, at winter wheat flowering and at the big flare stage of summer maize. Reducing pesticides by 35–65% had no adverse effect on crop yields, and thus had the potential to reduce the costs of pest control and produce the greatest economic benefit. When no pesticides were used in the insect‐trapping lamp control area, the annual yield was still >15 t hm ‐2 . CONCLUSION: If pesticides are used in a timely fashion and at the appropriate stage, their use may be greatly reduced with the help of an insect‐trapping lamp. © 2018 Society of Chemical Industry Abstract : Physical methods to control pests are being paid more attention. This study demonstrated that pesticides used in a timely fashion and at appropriate stages could be greatly reduced with the help of insect‐trapping lamps.